Potential Development of Shredded Fish Products in The Kendari Permata Image Industry in Purirano Village Kendari District Kendari City - Arrazaq, Muhammad; Pandangaran, Ayub M.; Syukri, Muhammad (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2020)
The results of this study show that shredded fish products in the Kendari Permata Industrial Industry show: 1) tuna shredded tuna products are greater than one with several 2.93> 1. In other words the R / C value of 2.933 is greater than one, while the marlin shredded product is also greater than one with the number 2.67> 1. In other words, the R / C value of 2.676 is greater than one, and for shredded tuna products that is 1.78> 1 with more than one number. In other words, the R / C value of 1,784 is greater than one, so it can be concluded that skipjack tuna, marlin, and tuna products are profitable and feasible to be developed.e 2) Aspects that can be developed according to consumers in general are the addition of packaging types of canned and dried products, the addition of shredded fish products such as milkfish, catfish and carp and other flavor enhancements such as sweet and spicy to add flavor to shredded fish products.